Penyuluhan Pencegahan Penyakit Skabies dan Pola Hidup Bersih dan Sehat (PHBS) Kepada Santri Putra dan Putri Pondok Pesantren Nurul Hakim Kediri Lombok Barat - Yuliansyah, Lalu Fauzan Adi (Universitas Mataram, 2023)
Scabies disease in Islamic boarding schools is still common. Several research results show that prevention of scabies is more important than treatment. Prevention of scabies is more effective if done through education. Disease prevention education provides knowledge and information that ultimately changes attitudes and behavior to be more hygienic so that it can prevent various diseases, including scabies. Clean and Healthy Living Behavior (PHBS) can be a solution that must be implemented in the Pondok environment. This service aims to provide education about preventing scabies through PHBS to male and female students at the Nurul Hakim Islamic boarding school, Kediri, West Lombok. The implementation stages include lectures, discussions, simulations, providing facilities for PHBS activities and forming the commitment of the students to implement PHBS in the Islamic boarding school environment. Service activities have been carried out well. Every party was very enthusiastic, both the students and the boarding school administrators. The output of service activities is in the form of knowledge and understanding about PHBS, students' skills in making creative posters and washing hands properly, PHBS facilities in the form of toiletries and brushing teeth, medicines for scabies. PHBS activities need to be maintained because they provide benefits to students in the form of improving health status and increasing learning and work productivity.